Inside Cover: A Chemical Tool for In Vitro and In Vivo Precipitation of Lysine Methyltransferase G9a (ChemMedChem 3/2014). Issue 3 (March 2014) - Konze, Kyle D.; Pattenden, Samantha G.; Liu, Feng; Barsyte‐Lovejoy, Dalia; Li, Fengling; Simon, Jeremy M.; Davis, Ian J.; Vedadi, Masoud; Jin, Jian
<x xml:space="preserve">Abstract</x> The inside cover picture shows chem‐ChIP, a method to examine occupancy of the lysine methyltranferase G9a on chromatin. UNC0965 (green) bridges streptavidin‐coupled magnetic beads (blue and yellow) and G9a (magenta). UNC0965 is cell permeable, which gives chem‐ChIP a distinct advantage over traditional in vitro antibody ChIP. For further details, see the Communication by Jian Jin et al. on p. 549 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>